ANALYSIS OF THE DEVELOPMENT OF THE CONSTRUCTION INDUSTRY AS A PREREQUISITE FOR REALIZING ITS EXPORT POTENTIAL - Volodymyr Dalyk; Ivan Zapisotskyi (Global Prosperity, 2025)
The development of the construction industry is one of the key factors in economic growth, infrastructure modernization, and enhancing the investment attractiveness of a country. In the context of globalization and increasing competition in the international market, the construction sector has significant potential for expanding export activities, which, in turn, can contribute to greater economic stability and international competitiveness of the national economy. At the same time, the realization of the export potential of the construction industry faces a number of challenges, including regulatory constraints, lack of investment, technological lag, and institutional barriers. The aim of this study is to analyze the development of the construction industry as a prerequisite for increasing its export potential and to identify strategic directions for strengthening the competitiveness of the sector at the international level. To achieve this goal, a systemic approach, statistical analysis methods, comparative analysis, and modeling were used. The study examines the theoretical foundations of the development of the construction industry, its impact on the country's economy, and the key factors determining the sector’s export potential. A comprehensive analysis of the current state of the construction sector in Ukraine has been conducted, identifying key trends and challenges in its development. Based on the obtained results, the main barriers hindering the export activity of construction enterprises have been identified, including economic policy instability, the lack of effective financial support mechanisms for exporters, insufficient technological development, and inadequate workforce qualification levels. The research findings can be used to develop government policies aimed at enhancing the export capacity of the construction industry and its integration into global markets.